Labor Market Reform and the Cost of Business Cycles - Tom Krebs; Martin Scheffel (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the effect of labor market reform on the welfare cost of business cycles. Motivated by the German labor market reforms of 2003-2005, the so-called Hartz reforms, the paper focuses on two labor market institutions: the unemployment insurance system determining search incentives and the system of job placement services affecting matching efficiency. The paper develops a tractable search model with idiosyncratic labor market risk and risk-averse workers, and derives a closed-form solution for the welfare cost of business cycles as a function of the various parameters of interest. An improvement in job placement services leads to a reduction in the welfare cost of business cycles, but a change in unemployment benefit generosity has in general an ambiguous effect. A quantitative analysis based on a calibrated version of the model suggests that the German labor market reforms of 2003-2005 reduced the non-cyclical unemployment rate by 3 percentage points and reduced the welfare cost of business cycles by 30 percent.
Keywords: E20; J20; E30; 330